Maya : - Lanier, Lee (Wiley Publishing, Inc., 2007)
Designed for busy Maya users like you, this guide offers dozens of how-tos, workarounds, and shortcuts culled from years of experience in a fast-paced, deadline-driven production pipeline. You’ll discover tricks and timesavers on texturing particles, customizing Paint Effects brushes, modeling polygon faces, creating facial rigs with wire deformers, and much more—and helpful full-color illustrations reinforce the concepts. From modeling, animating, and rigging to texturing and lighting, this book will help you streamline workflow and improve your skills.